2012
DOI: 10.1038/jhg.2011.152
|View full text |Cite
|
Sign up to set email alerts
|

Myotonic dystrophy type 2 is rare in the Japanese population

Abstract: Figure 1 Repeat-primed PCR analysis. Expanded CCTG repeats in the two DM2 patients (Caucasian and Japanese DM2 9 in lanes 4 and 5, respectively) are detected as a continuous characteristic smear of products at higher molecular weight than those in non-DM2 patients (3 different individuals from the 11 patients showing a single allele by PCR amplification of the DM2 repeat in lanes 1-3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In this study, we report our 14-year experience in DM2 genetic testing as one of the main Italian reference centers for the molecular diagnosis of myotonic dystrophies. The prevalence of DM2 likely varies by population: DM2 is rare in the Japanese population ( Matsuura et al, 2012 ), and in the United States, clinical experience suggests that DM2 is roughly fivefold less common than DM1 ( Thornton, 2014 ; Meola and Cardani, 2015 ). Data about the prevalence of DM2 in Europe are limited except for the German and Finland populations, where it may be like that reported for DM1 ( Suominen et al, 2011 ; Mahyera et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we report our 14-year experience in DM2 genetic testing as one of the main Italian reference centers for the molecular diagnosis of myotonic dystrophies. The prevalence of DM2 likely varies by population: DM2 is rare in the Japanese population ( Matsuura et al, 2012 ), and in the United States, clinical experience suggests that DM2 is roughly fivefold less common than DM1 ( Thornton, 2014 ; Meola and Cardani, 2015 ). Data about the prevalence of DM2 in Europe are limited except for the German and Finland populations, where it may be like that reported for DM1 ( Suominen et al, 2011 ; Mahyera et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study in Rome province, Italy, identified a total of 40 DM2 cases with a population size of 4,039,813, resulting in a prevalence of 0.99 cases per 100,000 [26]. There was a large difference in the reported DM2 prevalence, which may be explained clinically by the diagnosis delay resulting from the late-onset age and atypical symptoms as well as genetically by the diagnosis difficulty due to the high instability and variability of CCTG repeats in CNBP [44, 45]. Due to its prevalence in non-European populations, DM2 is a rare disease, and only a few cases have been reported in Japan [46], India [47], and Afghanistan [48].…”
Section: Discussionmentioning
confidence: 99%
“…DM2 is known to be prevalent in Caucasians [13][14][15]. However, it seems to show ethnic differences as a recent Japanese study failed to identify a single DM2 patient with expanded CCTG repeats in the CNBP gene among undiagnosed limb-girdle muscular dystrophy patients or undiagnosed patients with electrical or clinical myotonia [16]. Furthermore, no report on DM2 has ever been issued in South Korea.…”
Section: Discussionmentioning
confidence: 99%